Rural Electrification in Central America and East Africa, two case studies of sustainable microgrids - Andrea MICANGELI; Riccardo DEL CITTO; Francesco CHECCHI; Daniele VIGANÒ; Serge NOUBOUNDIEU; Giulia CESTARI (Revista Iberoamericana de Estudios de Desarrollo)
This paper deals with the electrification of rural villages in developing countries using Sustainable Energy Systems. The rural electrification feasibility study is done using Hybrid Optimization Model for Electric Renewable PRO (HOMER PRO). The HOMER PRO energy modelling software is an optimization software improved by U.S. National Renewable Energy Laboratory. It helps in designing, comparing and optimizing the design of power generation technologies. In this paper, two rural electrification case studies are modelled and analysed using HOMER PRO. Technical and economic evaluation criteria are applied to study the feasibility of a micro-hydro plant in El Díptamo (Honduras), and a hybrid plant composed of photovoltaic module arrays, Diesel generators, and flow batteries, in a small island on Victoria Lake. For both cases, we show the results of the studies of the daily and yearly loads, of the resources available in the area and the economic evaluation of the chosen plants configuration.